Paraconsistent artificial neural networks and EEG analysis. (6th September 2011) - Abe, Jair Minoro; Lopes, Helder Frederico da Silva; Anghinah, Renato
The aim of this paper is to present a study of brain EEG waves through a new ANN (artificial neural networks) based on Paraconsistent Annotated Evidential Logic, Eτ, which is capable of manipulating concepts like impreciseness, inconsistency, and paracompleteness in a nontrivial manner. As an application, the Paraconsistent Artificial Neural Network (PANN) proved capable of recognising children with Dyslexia with Kappa index at a rate of 80%.